2023
DOI: 10.3390/physics5010011
|View full text |Cite
|
Sign up to set email alerts
|

Heating and Cooling in Transversely Oscillating Coronal Loops Powered by Broadband, Multi-Directional Wave Drivers

Abstract: Recent studies have identified the potential for coronal wave heating to balance radiative losses in a transversely oscillating low-density loop undergoing resonant absorption, phase mixing and the Kelvin–Helmholtz instability. This result relied on a continuous, resonant oscillatory driver acting on one of the loop footpoints and similar setups with non-resonant driving produce insufficient heating. Here, we consider broadband and multi-directional drivers with power in both resonant and non-resonant frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…To achieve an efficient energy flux, a driver with an eigenfrequency is a common choice. However, from a more realistic perspective, the use of a broadband driver has been discussed, for instance, by Afanasyev et al (2019), Pagano et al (2020), Howson & De Moortel (2023). In this case, the resonant component of the broadband driver can be selected by the loop, thus facilitating efficient energy injection.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…To achieve an efficient energy flux, a driver with an eigenfrequency is a common choice. However, from a more realistic perspective, the use of a broadband driver has been discussed, for instance, by Afanasyev et al (2019), Pagano et al (2020), Howson & De Moortel (2023). In this case, the resonant component of the broadband driver can be selected by the loop, thus facilitating efficient energy injection.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Many observations show that an enhanced power occurs at ∼3 mHz in the coronal velocity power spectrum, implying that the observed transverse waves may be excited by p-modes (e.g., Van Doorsselaere et al 2008;Tomczyk & McIntosh 2009;Morton et al 2015Morton et al , 2016Morton et al , 2019. Such a power spectrum has also been used to drive kink oscillations in simulated coronal loops (e.g., Pagano & De Moortel 2019;Howson & De Moortel 2023). Meanwhile, wave excitation by p-modes is also widely studied in a number of analytical and modeling works.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of footpoint-driven transverse waves with a multi-frequency spectrum in the energy evolution and heating of 3D coronal loops has also been studied in recent years (e.g. Pagano & De Moortel 2019;Pagano et al 2020;Howson & De Moortel 2023). However, no numerical study of 3D coronal loops perturbed by broadband drivers has reported on the excitation and evolution, spatial and temporal, of standing waves matching the observed decayless oscillations, in the presence or absence of a transition region and a lower chromosphere.…”
Section: Introductionmentioning
confidence: 99%